ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KUALITAS INFORMASI PELAPORAN KEUANGAN PEMERINTAH DAERAH KABUPATEN JEMBRANA - Kusuma, Febry Perdana; Yasa, I Nyoman Mahaendra; Djayastra, I Ketut (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.05.NO.12.TAHUN 2016, 2016)
Accountability is responsibility form of success of failure of organization mission in reaching its purpose and target as stated previously. The form of goverment responsibility is monetary report. Information being displayed should be beneficial and can be understood by its users. The quality of monetary report can show the quality of goverment during a period. Questionnaire is used in collecting the data. Its given toward Financial Management ( User Administration Budget , Finance Officer , and Treasurer ) on regional work units (SKPD) . The population used was the financial manager in each SKPD by sampling with quota sampling and purposive sampling each t hree respondents in each SKPD . The Quality of Human Resources, Monetary Control, The Use of Information Technology influence indirectly toward The Quality Information of Local Goverment Monetary Report of Jembrana Regency, through intervening variable that is Intern Control System.
Keywords: The Quality of Human Resources, Monetary Control, The Use of Information Technology, Intern Control System, The Quality Information of Local Goverment Monetary Report